A retrospective multicenter study comparing metal–ceramic and composite single crowns performed in public general dentistry: 5-year results. Issue 1 (1st January 2016) - Overmeer, Jennie; Narby, Birger; Hjalmarsson, Lars; Arnrup, Kristina; Eliasson, Alf
Abstract: Objective The aim of this study was to evaluate and compare the 5-year survival and complication rate of metal–ceramic (MC) and composite single crowns performed within Public Dental Service, general dentistry, in three Swedish counties and with patients' gender, tooth position, root canal treatment and the presence of a post-and-core taken into account. Methods Data were collected from dental records of 600 patients who had received either an MC ( n = 300) or a composite ( n = 300) crown on a premolar or molar tooth in the year 2005 and where 5 years of follow-up data were available. Status at treatment completion and at follow-up was recorded, together with any history of intervention during the follow-up period. Results The 5-year survival rate for MC crowns was higher than for composite crowns (93% versus 70%; p < 0.001). This difference was stable, irrespective of the county, patients' gender or tooth position. No gender difference in survival rate was seen for MC crowns, while the survival of composite crowns was significantly higher among women than among men (75% versus 65%; p < 0.05). For MC crowns, there was a tendency toward a lower survival rate for endodontically treated teeth without a post-and-core (83%) as compared to those provided with a post-and-core (93%) and to vital teeth (94%). Surviving composite crowns had recordings of significantly more complications than MC crowns ( p < 0.001). Conclusion On premolars and molars, MC crowns have a better medium-term prognosis and fewer complications than composite crowns.